WORD OF MOUTH DAN PERANAN CIRI PRODUK INOVASI - Vincent Tarmudji; Rayini Dahesihsari (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2013)
While innovation is important in our daily life, as a matter of fact many innovation has failed to be accepted. Word of mouth has been wellknown as one among the most effective strategy for innovation adoption. Word of mouth (WOM) is defined as one example of communication pattern which involve individuals or groups, when they talk about their preferences about some product. Despite the importance of WOM, little attention has been given to understand how and why effective WOM induce adoption of innovation products. The purpose of this research is to explore the contributions of innovation attributes on WOM, using the diffusion of innovation theorethical framework. These innovation attributes are measured from the perception of the user of the product. In this research, the innovative product used as the case is the Dropbox application. The data of 156 respondents of Dropbox user was collected using the accidental sampling techinique. Using the multiple linear regression analysis, the result shows that amount of WOM can be influenced by how easily the benefit of the innovation can be seen (observability attribute) and how simplicity the innovation is (complexity attribute). Meanwhile for the valence of WOM (positive or negative) is influenced only with the observability attribute. The research indicates that it is important for companies to show the result of their innovation through opinion leader who have close connection with the target of consumer so the observability attribute from the innovative product can be seen. Companies also need to consider the complexity attribute of their innovation. Attribute of complexity can indeed increase the amount of WOM but might lead to the negative discussion which would be contraproductive for the adoption of the innovation.